EVALUASI PENERAPAN PENGAKUAN DAN PENGUKURAN PENDAPATAN PSAK 72 PADA PT PRIMA MULTI TERMINAL: Evaluation Of Accounting Application Recognition And Measurement Of Revenue Of PSAK 72 At PT Prima Multi Terminal - Ayu Sukmawati; Juliana Nasution (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Revenue recognition needs to be recognized promptly, so as not to cause errors in presenting information or data in company reports when making decisions. When viewed based on the five-step model of IFRS, it is not by the revenue recognition principle. The purpose of this study was to determine how the application of PSAK 72 to the recognition of contract revenue with customers at PT Prima Multi Terminal. The analytical method used in this research is descriptive qualitative which aims to describe the data that has been collected as it is obtained from the results of interviews and data collected from the company. The results of the study indicate that PT Prima Multi Terminal has complied in recognizing revenue with PSAK 72.